Increasing the capacity of family planning cadres using ABPK in Puskesmas Lepasan, Bakumpai District - Laurensia Yunita; Onieqie Ayu Dhea Manto; Fadhiyah Noor Anisa (Universitas Muhammadiyah Magelang, 2024)
Indonesia is projected to experience a significant population increase by 2035. The Family Planning (KB) Program is a key control measure. KB cadre involvement is crucial for providing information and motivation to potential acceptors. However, enhancing cadre counseling capacity, particularly using Counseling Demonstration Tools (ABPK), remains essential. This community service aimed to improve KB cadre knowledge and skills in providing contraceptive counseling using ABPK. Methods included counseling, mentoring, and distributing ABPK pocketbooks to cadres. Evaluations measured pre- and post-activity cadre knowledge increases. Results showed a significant rise in cadre knowledge about contraception and ABPK use, with the percentage of cadres demonstrating good knowledge increasing from 33.3% to 87%. This improvement is expected to impact contraceptive use within the Lepasan Health Center's area.